FAKTOR-FAKTOR YANG MEMPENGARUHI KEINGINAN RUMAH TANGGA MISKIN DALAM MENYELESAIKAN PENDIDIKAN DASAR PADA DAERAH PERKEBUNAN DI KABUPATEN PASAMAN - Yulia Anas (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2014)
Abstract: This Research aims to know the factors influencing the willingness of poor household in completing basic education in the region in Pasaman plantations. By using Logistical Regression analysis and descriptions analysis, the factors influencing  the willingness of poor household in complete primary education in the area of plantations in Pasaman are household income and expenditure allocation for education is low. Based on the research obtained, that opportunities are increasing household incomes to complete primary education same as the household incomes remain. Its mean that mean household income changes have no effect on households in completing primary education. Based on research data average income households per month are Rp 1.433.900,-. With the average number of household members of 6 people so home appliances have difficulties to finance school, and it became one of the causes of children dropping out of school. Keywords: primary education completion, poor plantation area, household Abstrak:Riset ini bertujuan untuk menganalisis factor-faktor yang mempengaruhi keinginan rumah tangga miskin dalam menyelesaikan pendidikan dasar pada daerah perkebunan di Kabupaten Pasaman, menggunakan analisis regresi logistic dan analisis deskriptif. Hasil riset menunjukkan bahwa rendahnya pendapatan rumah tangga dan alokasi pengeluaran untuk pendidikan merupakan variable yang secara signifikan mempengaruhi kesediaan rumah tangga dalam menyelesaikan pendidikan dasar. Setiap peningkatan pendapatan rumah tangga memberikan peningkatan peluang untuk menyelesaikan pendidikan dasar. Rata-rata perubahan pendapatan rumah tangga tidak memiliki pengaruh dalam penyelesaian pendidikan dasar. Berdasarkan temuan riset terlihat bahwa rata-rata pendapatan rumah tangga per bulan adalah Rp 1.433.900,-. Dengan rata-rata anggota 6 orang, rumah tangga mengalami kesulitan mendanai pendidikan. Hal ini menjadi penyebab utama putus sekolah. Kata kunci: penyelesaian pendidikan dasar, daerah perkebunan miskin, rumah tangga